Comparative Study on Speaking Assessment Rubrics in Trinity and Cambridge Language Certificates - Lucia Fraga-Viñas; Maria Bobadilla-Perez (Acta Universitatis Sapientiae: Philologica)
The European Council has been instrumental in the standardization of language competence levels and certifications with the guidelines provided in the Common European Framework of Reference for Languages (CEFR) published in 2001 and later reviewed in 2020 with the Companion Volume with New Descriptors (CEFRCV). Cambridge Assessment English and Trinity College are two of the highest regarded institutions at the international level that grant their language certificates following the language competence levels provided by the CEFR. For this reason, the current study is grounded on the conviction that those certificates should meet certain principles of the Framework as a form of guarantee that they are assessing the CEFR level correctly. In particular, this paper focuses on the speaking skill and the rubrics of assessment used by the two aforementioned institutions. The rubrics of Trinity and Cambridge for the assessment of the oral production at the B2 CEFR level were considered for the purposes of this study – in particular, the rubrics that assess the oral production in the Integrated Skills in English (ISE-II) exam and in the First Certificate in English (B2 First). With a qualitative document research approach, this study analyses these rubrics in order to determine to what extent they respect the criteria established by the CEFR.